L’EPISTEMOLOGIA DELLA MEDICINA ELLENISTICA - Mario Vegetti (Lexicon Philosophicum)
Erophilus’ contribution to medical epistemology chiefly lies in his refusal to pursue the philosophy of nature, a refusal intended to ensure the autonomy of medicine. Medical theory must be limited to the field of observable phenomena, especially via anatomical dissection, and must avoid any discussion on the primary elements of matter. This approach was ultimately to pave the way to empiricism, which rejected anatomy itself, and was developed within the Erophilean school despite the rationalism of its founder. Erasistratus carried the rationalistic program further, starting with the drawing of a distinction between two levels of medicine, namely the scientific (aetiology and physiology) and the stochastic (diagnosis and therapy). Erasistratus’ main effort consisted in the systematic fine-tuning of the theory of physiology: it required the introduction of structures (triplokia, anastomosis) empirically unobservable but whose assumption was imposed by theory, making them “rationally observable” (logoi theoreta). In this way, Erasistratus was also able to make diagnosis and therapy somehow deducible from aetiology and physiology, thus completing the rationalist project. The models according to which Erasistratus conceived of structures and somatic processes were largely derived from contemporary Hellenistic technology, both mechanical, and hydraulic and pneumatic.